Kedudukan Pemegang Saham (Investor) Dalam Kepailitan Perusahaan Go Public - Ginting, Jamin (LAW REVIEW, 2005)
Shareholder of company that sells its shares to public and eventually has public shareholders, popularly know as go-public company, are the last to get the benefits if their company is declared insolvent, that is bankrupt. This condition certainly put the said Â people in a very weak position, whereas as investors they should enjoy more legal Â protection and not the opposite. By law the Governtment Institution for Investment called Bapepam is required to provide a disclosed information regulation for a go public company against which a banckruptcy is filed. This would assist the interested whether or not to join the company. This working paper concerns with the legally weak position of the shareholders. What legal basis are being based on this situation and how far do the laws and regulations give legal guarantee and security to the investors of a go-public company.